Pompeii - Ball, Karen (London Usborne, 2006)
Each title in this series contains a vivid evocation of a major historical catastrophe, in an easy-to-follow manner. 'Pompeii' recounts the tragic story of the Italian city that came to a sudden end upon the furious eruption of the volcano Vesuvius
Include Illustration
Keywords: Italy--Vesuvius -- Eruption of Vesuvius (Italy : 79) -- Italy--Pompeii (Extinct city)